PTH-116 Microscopic Colitis in Tayside – Further Observations on Clinical Features and outcome. (4th June 2013) - Heron, T; Mowat, C; Groome, M; Walsh, S; Siddhi, S; Meritsi, A
Abstract : Introduction: The aetiology of microscopic colitis remains unknown. We have previously reported our experience of microscopic colitis diagnosed in our region between 1999 – 2004(1). Although data continue to emerge, the natural history of microscopic colitis remains unclear. Furthermore, there are reports of macroscopic changes in the mucosa at endoscopy. Methods: Cases from 2004–2011 were identified from pathology records. Case notes were retrospectively reviewed and data extracted including subtype of microscopic colitis and clinical details where possible. Results: 82 case notes were obtained and reviewed. 8 cases did not have a clear diagnosis and were excluded. Of the remaining 74 cases, 56 were collagenous colitis, 18 lymphocytic colitis. 17 patients had macroscopic abnormalities (excluding diverticulosis) at endoscopy; 16 of these in the collagenous colitis group, representing 28% of this subgroup. The mean age was 46.1 (range 33–87), female: male ratio of 4.3:1. 18 reported an autoimmune condition including 2 coeliac disease and 7 hypothyroidism. 30(40%) were on a proton pump inhibitor at the time of diagnosis and 15(24%) were on non-steroidal anti-inflammatories. Follow up data was available for 66 patients. Of these 47(71%) reported complete resolution of symptoms and 15(22%) partial resolution. 5(7%) did not respond in the follow up period. Therapeutic strategies included either alone or a combination of stopping/switching PPI, loperamide, mesalazine and steroids. 24/47(65%) of complete responders required simple intervention (PPI withdrawal, switch in brand of PPI, loperamide or even spontaneous resolution) whereas 10/47(21%) required steroids. 7/15(47%) partial responders received steroids. Conclusion: Since microscopic colitis was last studied in our region, the female predominance has increased, the mean age has dropped by almost 20yrs, and the ratio of collagenous : lymphocytic colitis has increased from 2:1 to 3:1. This could represent a change in the number of younger people investigated or missing data in our cohort. A significant number of patients with a diagnosis of collagenous colitis had endoscopic abnormalities in comparison to the lymphocytic colitis group, which does raise the question of the nomenclature. The majority of patients have complete resolution of symptoms with simple intervention. Disclosure of Interest: None Declared. Reference: Microscopic Colitis in Tayside: Clinical features, associations and behaviour. Mowat C, Heron T, Walsh S. Gastroenterology 2005: 128 (4); A331